Obrazovanje: Kako unaprijediti djelotvornost i kavlitetu - Lasić-Lazić, Jadranka; Slavić, Aida (2002)
Although plan and programme of Information Sciences Department in Eightees was made by English and American model, it is still not very clear wheather this trend of development should be followed. Every planning concept of education is included in wider interrelated frameworks of education in whole. What is specific for Croatia is that average professional level of institutions (ans education of information professionals here is still connected to institution), if we think of library, archive and museum quality and it's management competence, is lower than in Western countires. There are two reasons why we try to develop education programs. Firt is the speed of economical, political and technological changes and the second is global connection of information society and joined market of working people, on which, tomorrow, our graduated information professionals, who we educate, will be.
Projekt MZOS
HRV